2006
DOI: 10.1177/154193120605002407
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Usability of Paper Ballots: Efficiency, Effectiveness, and Satisfaction

Abstract: The Help America Vote Act (HAVA) of 2002 secured funding for improvements to election administration. Improvements include upgrading older voting systems to meet new guidelines. To determine whether the new voting systems are improvements over existing voting systems, information is needed on the usability of the older, traditional systems. This study was designed as a first step in addressing the need for usability data on existing voting systems. Three traditional paper ballots were empirically evaluated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Overvotes in particular are most often attributed to ballot design, voting technologies, and the interaction of these factors with voter attributes (e.g., education, age, and related physical acuity). Here human factors interact with technology and ballot design to produce errors similar to those observed with the use and operation of consumer products Everett, Byrne, and Greene 2006;Laskowski et al 2004;Roth 1998).…”
Section: Previous Researchmentioning
confidence: 99%
“…Overvotes in particular are most often attributed to ballot design, voting technologies, and the interaction of these factors with voter attributes (e.g., education, age, and related physical acuity). Here human factors interact with technology and ballot design to produce errors similar to those observed with the use and operation of consumer products Everett, Byrne, and Greene 2006;Laskowski et al 2004;Roth 1998).…”
Section: Previous Researchmentioning
confidence: 99%
“…Problems deciphering ballots are not limited to the senior citizens of Palm Beach, Florida. In one study, researchers examined how different ballot types affected error rates and found that 11% of ballots cast by college undergraduates in an experiment contained at least one error (Everett, Byrne, & Greene, 2006). Furthermore, according to the Government Accountability Office (2014), ballot design can be a key factor in wait times.…”
Section: Ssues Related To Representation Spanmentioning
confidence: 99%
“…Overvotes are most often attributed to ballot design, voting technologies, and the interaction of these factors with voter attributes (e.g., education, age, and related physical acuity). Here, human factors interact with technology and ballot design to produce errors similar to those observed with the use and operation of consumer products Everett, Byrne, and Greene, 2006;Laskowski et al, 2004;Roth, 1998).…”
Section: How We Votementioning
confidence: 99%